Sentencing Guidelines and focal concerns: The effect of sentencing policy as a practical constraint on sentencing decisions - Crow, Matthew S. (American journal of criminal justice, 2006)
Contemporary research on criminal sentencing has analyzed sentencing under numerous sentencing policies, yet the effect of sentencing policy on outcomes and disparity is not known. A variety of sentencing guidelines systems, one of the more common sentencing policies, exists throughout the country. In addition, recent Supreme Court decisions regarding sentencing guidelines are likely to produce alterations to several state sentencing policies over the next few years. Using data from the state of Florida, the current study examines the effects of policy transformation on sentencing disparity within the focal concerns of sentencing perspective. The authors view sentencing guidelines as a practical constraint on sentencing decisions that influence other key variables. The results indicate that sentencing policy transformation has an important effect on both sentencing decisions and on the factors that shape those decisions. The findings suggest that future sentencing research and theoretical development would benefit from incorporating measures of policy differences in its analyses.